2020
DOI: 10.3390/molecules25215216
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis of Human Natural Killer Cell Derived Extracellular Vesicles for Identification of Anticancer Effectors

Abstract: Cancer immunotherapy is a clinically validated therapeutic modality for cancer and has been rapidly advancing in recent years. Adoptive transfer of immune cells such as T cells and natural killer (NK) cells has emerged as a viable method of controlling the immune system against cancer. Recent evidence indicates that even immune-cell-released vesicles such as NK-cell-derived exosomes also exert anticancer effect. Nevertheless, the underlying mechanisms remain elusive. In the present study, the anticancer potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 45 publications
2
47
0
Order By: Relevance
“…In addition to expressing typical exosome markers (e.g., CD63, Rab5b, and TSG101), most studies have used CD56 as a marker to identify NKEVs isolated from CD56 + NK cells. Additionally, receptors of NK cells such as natural killer cell P30-related protein (NKp30), NKp46, NKp44, NKG2D, and DNAM1 were shown to be expressed by NKEVs in some studies and may be useful for their identification (6,12,14,17). However, definitive markers have yet to be established as CD56 is not exclusive to NK cells and a subset of NK cells are CD56 − .…”
Section: Isolation and Definition Of Nkevsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to expressing typical exosome markers (e.g., CD63, Rab5b, and TSG101), most studies have used CD56 as a marker to identify NKEVs isolated from CD56 + NK cells. Additionally, receptors of NK cells such as natural killer cell P30-related protein (NKp30), NKp46, NKp44, NKG2D, and DNAM1 were shown to be expressed by NKEVs in some studies and may be useful for their identification (6,12,14,17). However, definitive markers have yet to be established as CD56 is not exclusive to NK cells and a subset of NK cells are CD56 − .…”
Section: Isolation and Definition Of Nkevsmentioning
confidence: 99%
“…For example, breast cancer cells (SKBR3) and melanoma cells (501mel) were shown to resist lysis of exosomes released by resting or activated NK cells even over a long period of coculture (6). However, it was later shown that exosomes derived from NK-92 MI cells had antitumor effects on melanoma both in vitro (B16F10 cells) and in vivo (8), and those isolated from IL-2/IL-15-activated NK cells showed cytotoxicity in breast cancer cell lines (MDA-MB-231/F and MCF-7) (12,15,16). The heterogeneous content of exosomes from different cellular sources may account for these inconsistent observations.…”
Section: Heterogeneity Of Nkevsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, NK cells not only directly kill compromised cells, but when properly activated, can be potent producers of TNF-a and IFN-g, the last one being a known inducer of PD-L1 expression. Alternative mechanisms by which NK cells were shown to carry out their anti-tumor function involve expression of death receptor ligands FasL and/or TRAIL (9)(10)(11)(12) and release of extracellular vesicles, such as exosomes, with cytotoxic activity (13) that contain effector miRNAs [reviewed in (14)], cytokines, and display NK cell surface receptors (15)(16)(17). In addition to direct killing, NK cells secrete chemokines and cytokines to recruit and coordinate responses by other immune cells, such as T cells (7) and dendritic cells (DCs), in the tumor microenvironment or site of infection and can prime the adaptive immune response for better viral or tumor control (5)(6)(7)(18)(19)(20)(21)(22)(23) [reviewed in (24)] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%